Technical Efficiency of Higher Educational Institutions: A Study of Affiliated Degree Colleges of Barak Valley in Assam, India (Journal of Asian Development Studies, 2014)
Higher educational institutions (HEIs) as producing units involve several tangible and intangible inputs as well as outputs, and these outputs contribute to economic development through development of human capital. In Barak Valley number of colleges is increasing day by day, but the success rates of most of the colleges are below average. Some of the colleges are either over utilising or under utilising their resources, which results in loss of output and inefficiency. The paper investigates the technical efficiency of HEIs in Barak Valley and analyses the factors which influences the output of the HEIs by using stochastic frontier analysis (SFA). It also compares the technical efficiency (TE) scores of National Assessment and Accreditation Council (NAAC) accredited HEIs with other HEIs and then compares the rank of the HEIs with respect to their TE scores and performance. The study reveals that NAAC accredited HEIs are more technically efficient and performing better than non-accredited HEIs.